Efficacy of chitosan nanoparticles and mesenchymal stem cells in rabbit models for sciatic nerve regeneration - Al-Haideri, Dhurgham H.; Al-Timmemi, Hameed A. (Iraqi journal of veterinary sciences, 2024)
Peripheral nerve injuries (PNI) are frequently caused by several circumstances, including trauma and iatrogenic operations, and there are limited therapy options to help with functional recovery. This study aimed to compare in vivo adipose-derived stem cells (ASCs) to chitosan nanoparticles (CS NPs) in rabbit sciatic nerve defect regeneration. Twenty healthy rabbits of local breed randomly enrolled in two equal groups split into two groups at random: The critical size defect was bridged with a 14 mm conduit from acellular bovine urinary bladder impacted with chitosan nanoparticles (CS NPs) semi-gel 1mg/ml as the first group, and the critical size defect was bridged with mesenchymal stem cells (MSCs) 5x106 in the second group. At the end of 56 and 112 days, assessment of the nerve regeneration, motor and sensory function, and histopathological assessment of the sciatic nerve were investigated. According to the findings, the motor and sensory capabilities of the sciatic nerve increased faster in the mesenchymal stem cells (MSCs) group. In the mesenchymal stem cells group repairing a 10mm sciatic nerve defect, histopathological examination revealed basophilic nuclei of proliferated Schwann cells with thick myelin sheath, suitable orientation nerve fibers, dense axon population, large axon diameter, nerve fiber myelination, and low fibrous tissue at the epineurium compared to chitosan nanoparticles (CS NPs). It is concluded that effect mesenchymal stem cells (MSCs) promote regeneration of the sciatic nerve defect compared to chitosan nanoparticles (CS NPs).